2020
DOI: 10.1155/2020/2824984
|View full text |Cite
|
Sign up to set email alerts
|

Tenacissoside H Induces Apoptosis and Inhibits Migration of Colon Cancer Cells by Downregulating Expression of GOLPH3 Gene

Abstract: Objective. Tenacissoside H (TDH) is a Chinese medicine monomer extracted from Marsdenia tenacissima extract (MTE), which has been confirmed to have antitumor effects, but its mechanism is still unclear. The aim of this study was to investigate the effect and mechanism of TDH on human colon cancer LoVo cell proliferation and migration and explore the correlation of TDH treatment with the expression of GOLPH3 and cell signaling pathways in LoVo cells. Methods. LoVo cells were treated with TDH at 0.1, 1, 10, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Given the role of GOLPH3 in promoting autophagy, we hypothesized that GOLPH3 suppresses Akt, which contradicts the conventional conception that GOLPH3 promotes Akt [ 29 ]. Interestingly, we confirmed our hypothesis and showed that GOLPH3 inhibited Akt phosphorylation at Ser473; this contradicts the majority of previous studies, which reported that GOLPH3 activates the Akt/mTOR signaling to accelerate cancer progression [ 40 , 58 , 59 ]. Previous studies have confirmed that mTOR is a major suppressive regulator of the autophagic process and is regulated by starvation, growth factors, and cellular stresses [ 60 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Given the role of GOLPH3 in promoting autophagy, we hypothesized that GOLPH3 suppresses Akt, which contradicts the conventional conception that GOLPH3 promotes Akt [ 29 ]. Interestingly, we confirmed our hypothesis and showed that GOLPH3 inhibited Akt phosphorylation at Ser473; this contradicts the majority of previous studies, which reported that GOLPH3 activates the Akt/mTOR signaling to accelerate cancer progression [ 40 , 58 , 59 ]. Previous studies have confirmed that mTOR is a major suppressive regulator of the autophagic process and is regulated by starvation, growth factors, and cellular stresses [ 60 ].…”
Section: Discussionsupporting
confidence: 61%
“…When Golgi apparatus stress is ameliorated, GOLPH3 expression decreases, and the phosphorylation of the PI3K/Akt/mTOR pathway is promoted [ 62 ]. Previous studies that found GOLPH3 promotes Akt in colon cancer were performed using the cell lines HCT-116 [ 40 ], LoVo [ 58 ], and SW620 [ 63 ]. To the best of our knowledge, no study has constructed and used GOLPH3-overexpressing and -silenced cell lines to investigate the impact of GOLPH3 on Akt in HCT-116 and HT-29 cells.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Moreover, TEH also induced apoptosis and reduced the invasion of colon cancer cells through downregulating GOLPH3 expression and activity of PI3K/AKT/mTOR and Wnt/β-catenin signaling pathways. 29 Our results suggest that TEH suppresses the expression of PI3K/Akt/mTOR signaling pathway and promoted autophagy-related proteins and cell apoptosis. And inhibiting PI3K/Akt/mTOR signaling pathway obviously dampened the anti-tumor role of TEH in HCC cells.…”
Section: Discussionmentioning
confidence: 58%
“…18,19 Tenacissoside H (TDH) is a monomeric extract of Marsdenia tenacissima that has been linked to a few pharmacological benefits, such as anti-inflammatory, antioxidant, and anti-tumour characteristics. [20][21][22] TDH was found to inhibit IL-1β, IL-6 and TNF-α expression and to mediate nitric oxide synthase, as well as inflammation and oxidative stress, thus modifying neurological recovery in mice with cerebral ischemia-reperfusion damage. 20 TDH, on the other hand, has not been studied for osteolytic bone diseases.…”
Section: Introductionmentioning
confidence: 98%
“…Chinese herbal medicines are clinically natural pharmaceuticals with proven clinical efficacy, and when used properly, they have significantly fewer adverse side effects than western medicine 18,19 . Tenacissoside H (TDH) is a monomeric extract of Marsdenia tenacissima that has been linked to a few pharmacological benefits, such as anti‐inflammatory, antioxidant, and anti‐tumour characteristics 20–22 . TDH was found to inhibit IL‐1β, IL‐6 and TNF‐α expression and to mediate nitric oxide synthase, as well as inflammation and oxidative stress, thus modifying neurological recovery in mice with cerebral ischemia–reperfusion damage 20 .…”
Section: Introductionmentioning
confidence: 99%